Vzgoja in izobraževanje za trajnostni razvoj kot vseživljenjski proces - Golob, Nika (AS. Andragoška spoznanja, 2009)
The enhancement of our knowledge about excessive burdens imposed on the natural environment, or rather about limitations of self-purification ability of ecosystems, has led from an awareness of the situation from fifty years ago to establishment of key directions, which must be included in all educational and learning prograrnmes at alllevels. The environmental education concept has grown into education for sustainable development, which has spread into all facets of human life and activities. Unfortunately, the practice does not meet the expectations which need to be fulfilled to ensure a sustainable future, our responsibility towards the generations to come. This was confirmed through a research study on drinking water as a key factor for achievement of the goals of education for sustainable development.
Keywords: izobraževanje odraslih; Lifelong learning; vseživljenjsko učenje; sustainable development; trajnostni razvoj; okoljska vzgoja